Fenomenologia da afetividade: um estudo a partir de Michel Henry - Praseres, Janilce Silva (2015)
This work has as purpose, from the thought of Michel Henry, contemporary French philosopher, afford a study on the phenomenology of affectivity, more specifically on henrianas investigations regarding affectivity, considering the essential notes investigated and formulated in relation life, phenomenology, in the case the Phenomenology of Life or Material Phenomenology, and passivity. The intended reflection aims to consider possibilities that arise for the contemporary phenomenological field. The main thesis to be defended and grounded is that the essence of phenomenology of life manifests itself in immanent way by means of the affectivity. It is investigating the foundations for a Phenomenology of Affectivity, thus presenting a conceptualization from the radical immanence of life. Affectivity, privileged subject in Henry's works, is reached or reaches a very special way the experience of radical subjectivity, which, according to our philosopher, the life essentializes up itself, affecting itself in the experience of self same, the radical immanence of his affectivity. Because the concrete truth of this movement is the life that proves herself. Which is realized in his pathos, in the subjectivity that is known, independent of any conceptual or sensitive approach, or of a intentional look, but life in the absolute probation of their intrinsic certainty, in a material meaning, in the materiality of his pure appear that gives us access to itself, made in the modalities of suffering and enjoy, in the revelation itself, in its pathos of passivity that is affected. In order to sustain the structure of his thought, which culminates in the formulation of the phenomenology of life, Henry's concern aims to open up new fields of inquiry about the effective fenomenalização the phenomenality as such and in the reversal of phenomenology, a rethinking on this, another direction, a material bias. Therefore, this work is based in the works of this philosopher, in particular L'Essence de la manifestation.